Calving distribution of the Teshekpuk caribou herd, 1994-2003 - Carroll, Geoff M.; Parrett, Lincoln S.; George, J. Craig; Yokel, Dave A. (Rangifer, 2005)
Parturient female caribou from the Teshekpuk caribou (Rangifer tarandus granti) herd (TCH) have been observed across the western North Slope, but most cows that were seen with calves during the calving period were in the area surrounding Teshekpuk Lake. During surveys conducted between 1994 and 2003, 155 (91%) of 171 collared cows seen with calves were within an area given protected status in the 1998 Bureau of Land Management Final Integrated Activity Plan/Environmental Impact Statement (IAP/EIS). The percentage of adult collared cows seen with a calf between 1994 and 2003 has ranged from 44% to 86%, with a mean of 66%. The years with the lowest percentage of collared cows seen with calves were 1997 (50%) and 2001 (44%). In 1997 most of the herd migrated much farther south than usual, and in 2001 unusually deep, persistent snow restricted spring migration, resulting in fewer cows returning to the traditional calving area during the calving period. When snowmelt dates were earlier, calving locations were farther north. Average standardized travel rates for parturient cows were significantly greater before they had calves (7.25 km/day) than after 3.89 (km/day). Geographically, protections granted by the 1998 BLM IAP/EIS appear to adequately cover the concentrated calving grounds, allowing for variance in the annual distribution of calving cows.